English Civil Wars 1642-1649 "A Study of Its Origins, events and the most Important Consequences" - Mohammedameen, Sipal S; Mahmada, Sipan S. (Journal of Duhok University, 2019)
The English historians agree that the civil English war had complex intellectual roots between the two most powerful forces in England, the parliament and the king. The struggle started between them when King Charles I dissolved the parliament in 1625. This happened because the parliament refused to provide the king with the money he asked for his war with Spain. Besides, the English Parliament, led by John Beam, felt that the king favored the Roman Catholic, especially after his marriage from the French Roman Catholic princess Henrietta Maria in the 1st of May 1625. It is worth mentioning that the English civil war constantly and directly held balance of powers between the king and the parliament in England. Power and politics were two vital factors for social standards in England in the third and fourth decades of the seventeenth century. This was the beginning of struggle between the parliament and the king. Although the discussions between the two sides continued until March 1641, the king’s insistence on his individual political decisions without taking the English parliament approval along with the religious conflicts referred to the inevitability of war between the two sides.